Accuracy of the tritonwear unit in high performance swimmers - Campbell, A.; McKenna, M.; Sheath, M.; Scott, B.; Lobb, C. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Wearable devices to record swimming metrics are widely available but there is limited and contrasting evidence of the accuracy and validity of these devices (Morais et al. 2022). The purpose of this study was to evaluate the validity and accuracy of the 2022 version of the TritonWear (TW) sensor to assess swimming performance metrics (e.g., time, stroke rate (SR), distance per stroke (DPS)) in high performance swimmers.